Maximum entropy production principle in forest dynamics modelling - Lisitsyn, Viktor; Matveev, Nikolai; Kamalova, Nina; Evsikova, Natalya (BIO web of conferences, 2024)
Forest ecosystems are vivid representatives of open non-equilibrium systems. The existence of extreme principles in “ecological thermodynamics” is a subject of discussion in the works of many physicists, ecologists and researchers dealing with non-equilibrium thermodynamics. At the same time, the problem of the connection between the principles of maximum and minimum entropy production has been studied in detail enough in the works of L. M. Martyushev et al. However, for forest ecosystems, the works that point out the connection of these fundamental principles are clearly insufficient. Usually, these principles are opposed to each other. In the proposed work, within the framework of a unified approach, the dependencies of the entropy production density and the entropy density have modeled using the example of a pine ( Pínus sylvestris ) stand of the 1-grade forest site capacity. It has shown that entropy production and entropy production density take both maximum and minimum values in the process of ecosystem evolution.